The development on social science textbook based of e-book - Agustinova, Danang Ade; Rokhim, Hanif Nur (Universitas Negeri Yogyakarta, 2024)
The research aims to produce a social studies e-book with a blended learning model< an i=4> for class VIII students by describing (1) the process of developing a social studies e-book, (2) the feasibility of a social studies e-book product, (3) the effectiveness of the e-book Social Sciences. This research uses Research and Development (RnD) research with the steps of developing the ADDIE model. The ADDIE model consists of five steps, namely: (1) analysis (analyzing), (2) design (design), (3) development (development), (4) implementation (implementation), and (5) evaluation (evaluation). Social Studies is considered suitable for the social studies learning trial process. Referring to expert assessments: (a) media expert in the outstanding category, (b) material expert in the outstanding category, (c) teacher response in the outstanding category, (d) response from students in category group small is excellent, (d) the response of students in the large category group is good. (3) The results of the field trial showed that the scores of students who completed the KKM increased, from 17.85% at the pre-test stage and 82.15% at the post-test stage. The results of the hypothesis test also stated that Ho was rejected and Ha was accepted, which means that there is a significant difference in student learning outcomes. So, social studies e-books with a blended learning model are declared effective for use in learning. Collecting social studies e-books includes references, material preparation, video recording, editing and merging, and the completion process.